Gender Invariance and Psychometric Properties of the Nonproductive Thoughts Questionnaire for Children. (December 2019) - Kocsel, Natália; Mónok, Kata; Szabó, Edina; Morgan, Antony; Reinhardt, Melinda; Urbán, Róbert; Demetrovics, Zsolt; Kökönyei, Gyöngyi
Perseverative cognitions—rumination and worry—can contribute to mental and somatic health problems in adolescence. Girls usually report stronger rumination or worry than boys even in earlier years across the development age spectrum. Our aim was to test the gender invariance and psychometric properties of the Nonproductive Thoughts Questionnaire for Children (NPTQ-C). Study 1 involved 1, 572 students (mean age = 15.39 years, SD = 2.26; 49% boy) recruited representatively from local schools. We applied confirmatory factor analysis (CFA) to test the measurement model of perseverative cognitions. The gender invariance of the measurement model and the convergent validity were analyzed as well with CFA with covariates model. The original one-factor structure of NPTQ-C was supported in our adolescent sample. Gender invariance was also confirmed. The NPTQ-C indicated high convergent validity: showing positive correlations with emotional instability and emotional symptoms. In Study 2 (385 students; mean age = 16.05; SD = 1.23; 34% boy), we tested the construct validity of NPTQ-C. The applied CFA with covariates model supported the construct validity. In summary, NPTQ-C proved to be a good instrument for measuring ruminative and worrying thoughts of adolescents, which reliably measures perseverative cognitions across genders.